The Influence of Competency Development and Work Motivation on The Performance of KSP Coblong Pamor Employees - Sudana, I Ketut; Kresna Wirawan, I Dewa Gede; Siti Firmani, Putu (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
The research with the title